Challenges associated with the introduction of procedures for the validation of non-formal and informal learning in Germany : Results of a Delphi Scenario - Gutschow, Katrin [Verfasser]; Jörgens, Julia [Verfasser] ([Barbara Budrich], 2018)
The call for greater account to be taken on the labour market of non-formal and informal learning now enjoys a broad degree of consent in Germany. A BIBB research project has developed scenarios to depict relevant procedures which could be established in Germany over the course of the coming years. A Delphi survey was conducted, in which experts in some cases gave a critical assessment of the opportunities for the implementation of these scenarios. However, despite all the obstacles, preferred procedures were identified. When combined, these fulfil the expectations of respondents with regard to the identification, documentation, evaluation and certification of non-formal and informal learning. (BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; Informelles Lernen; Non-formales Lernen; Anerkennung; Befragung; Szenario